2013
DOI: 10.1007/s11655-013-1320-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of early treatment on 52 patients with preneoplastic hepatitis B virus-associated hepatocellular carcinoma by compound Phyllanthus Urinaria L.

Abstract: Anti-URG11, anti-URG19 and anti-DRG2 could be used as early markers in the prediction of the therapeutic efficacy of CPUL in treating preneoplastic HCC. CPUL is useful in preventing or delaying the development of HBV-associated cirrhosis to HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
14
2
Order By: Relevance
“…In our previous bioinformatic analysis, we found that VWCE was low expressed in breast cancer based on online analysis tools. These results are not consistent with the previous studies in other tumors [13,14,32,33]. We speculate that it may be related to the role and mechanism of the same gene in different tissues and cells, that is, malignant tumors are highly heterogeneous.…”
Section: Discussioncontrasting
confidence: 98%
“…In our previous bioinformatic analysis, we found that VWCE was low expressed in breast cancer based on online analysis tools. These results are not consistent with the previous studies in other tumors [13,14,32,33]. We speculate that it may be related to the role and mechanism of the same gene in different tissues and cells, that is, malignant tumors are highly heterogeneous.…”
Section: Discussioncontrasting
confidence: 98%
“…Once the treatment is stopped, the recurrence rate is 10.4–13.4% respectively (Cheng et al, 2009 ). Tong et al ( 2014 ) reports that compound in capsule of P. urinaria L. suppresses development of hepatocellular carcinoma (HCC) through an improved immune system, reversion of liver fibrosis, blockage of the induced hepatocarcinoma cell cycle and inhibition of angiogenesis. The HBV-DNA levels decrease ≥2 log in 22.2% (10/45) of patients in the treatment group compared with the control group at 5.0% (2/40).…”
Section: Clinical Trials Of P Urinaria Preparatiomentioning
confidence: 99%
“…The HBV-DNA levels decrease ≥2 log in 22.2% (10/45) of patients in the treatment group compared with the control group at 5.0% (2/40). The number of antibodies that test positive in the treated group is lower (1.08 ± 1.01) after the treatment period of 24 months compared with the control group (2.11 ± 1.12) (Tong et al, 2014 ). The anti-URG11 (33/52) and anti-URG19 (31/52) in both treated and control groups are over 60% at base line.…”
Section: Clinical Trials Of P Urinaria Preparatiomentioning
confidence: 99%
“…It is a formula used for HCC, especially HBV-related HCC in China. In our previous studies, we have elucidated that CP could reduce the expression of HBxAg in transplant tumors, and we also verified that CP could inhibit HBV-DNA replication and reduce the expression of URG4, URG7, URG11, and URG9, preventing and delaying the development of HBV-related HCC in patients treated with CP for two years [16–18]. Other scholars proved that CP could inhibit expressions of HBsAg and HBeAg, and it also could enhance the immune response in vivo and in vitro [19].…”
Section: Discussionmentioning
confidence: 80%